A Literature Review on the Continuing Professional Development (CPD) for Accounting Teachers: Perspective of Government Colleges in Bangladesh (Global Journal of Management and Business Research, 2022)
Teachers Continuing Professional Development CPD is a highly discussed issue nowadays all over the world due to its significant role in upholding the professional skills of the faculties Continuing professional development CPD is easy to recognize but relatively difficult to define because due to its formal and informal practices the scope and concept of the CPD surround theoretical and empirical controversy Dissimilar concepts of formal training and in-service learning make the issue more confusing However Day s 1999 definition of CPD covers each behavior that is aimed to bring changes in the classrooms In Bangladesh teachers continuing professional development CPD is yet to get appropriate attention from teachers themselves institutional authorities and education policy planners This study aims to examine the existing literature on the CPD of accounting teachers and particularly concentrate on the perspective of the government colleges in Bangladesh In the end this study puts forward specific recommendations for training providers policymakers and educational institutions to implement more CPD programs for accounting teachers in Bangladesh
Keywords: CPD; teaching; accounting; bangladesh